Representation of Food Image in the Poem of Spice Boy: Ari Ambarwati's Work as a Gastronomic Study - Setiawan, Bagas; Ma'arif, Moh Syamsul (Universitas Muria Kudus, 2025)
This study aims to analyze the representation of food images in the poem